2023
DOI: 10.1186/s40478-023-01566-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-Cov-2 infection and neuropathological findings: a report of 18 cases and review of the literature

Abstract: Introduction COVID-19-infected patients harbour neurological symptoms such as stroke and anosmia, leading to the hypothesis that there is direct invasion of the central nervous system (CNS) by SARS-CoV-2. Several studies have reported the neuropathological examination of brain samples from patients who died from COVID-19. However, there is still sparse evidence of virus replication in the human brain, suggesting that neurologic symptoms could be related to mechanisms other than CNS infection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 74 publications
2
2
0
Order By: Relevance
“…The presence of viral RNA and protein, using quantitative reverse-transcriptase PCR, and immunocytochemistry with primers, probes and antibodies directed against the spike and nucleoprotein regions, found low but detectable viral RNA levels in brain tissue but were unable to detect immunohistochemical evidence of viral particles [ 75 ]. On the other hand, another autopsy study provided evidence for peri-vascular hemosiderin-laden macrophages and hypoxic-ischemic changes in neurons [ 52 ], which we also observed (data not shown). Although immunostaining for SARS-CoV-2 viral spike and nucleoprotein was seen in a single brain, PCR revealed SARS-CoV-2 RNA in all brains [ 52 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The presence of viral RNA and protein, using quantitative reverse-transcriptase PCR, and immunocytochemistry with primers, probes and antibodies directed against the spike and nucleoprotein regions, found low but detectable viral RNA levels in brain tissue but were unable to detect immunohistochemical evidence of viral particles [ 75 ]. On the other hand, another autopsy study provided evidence for peri-vascular hemosiderin-laden macrophages and hypoxic-ischemic changes in neurons [ 52 ], which we also observed (data not shown). Although immunostaining for SARS-CoV-2 viral spike and nucleoprotein was seen in a single brain, PCR revealed SARS-CoV-2 RNA in all brains [ 52 ].…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, another autopsy study provided evidence for peri-vascular hemosiderin-laden macrophages and hypoxic-ischemic changes in neurons [ 52 ], which we also observed (data not shown). Although immunostaining for SARS-CoV-2 viral spike and nucleoprotein was seen in a single brain, PCR revealed SARS-CoV-2 RNA in all brains [ 52 ]. In another autopsy study, confocal imaging of sections stained for fluorescence, RNAscope, and immunohistochemistry demonstrated extracellular SARS-CoV-2 virions but failed to show viral particles in the brain parenchyma or olfactory bulb [ 50 ].…”
Section: Discussionsupporting
confidence: 85%
“…Meinhardt et al ( 3 ) reported SARS-CoV-2 RNA in the olfactory bulb ( 3 ). Lebrun et al reported SARS-CoV-2 RNA positivity in the brain by PCR in all ( n = 18) analyzed cases, while only one patient harbored SARS-CoV-2 viral proteins in the brain tissue ( 30 ). Solomon et al ( 11 ) achieved mixed results and argued that samples might have been contaminated by blood ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of this is infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, the etiological agent of coronavirus disease 2019 (COVID-19). Although SARS-CoV-2 was originally hypothesized to induce neurological symptoms, such as loss of smell and taste and altered consciousness, through direct infection of the brain, multiple case reports demonstrate little to no virus within the CNS compartment, including among patients that died due to severe disease ( Schurink et al, 2020 ; Fullard et al, 2021 ; Thakur et al, 2021 ; Lebrun et al, 2023 ; Song et al, 2023 ). Virus has been reported in brain endothelium or olfactory epithelium/mucosa in infected human subjects and non-human primates (NHPs), however, this does not extend to cells residing within the brain parenchyma ( Meinhardt et al, 2021 ; Thakur et al, 2021 ; Rutkai et al, 2022 ).…”
Section: Systemic Inflammationmentioning
confidence: 99%